Evaluating the Suitability of the Requirements For Adopting International Financial Reporting Standard Ifrs 18 In the Banking Sector and Its Impact on Enhancing the Quality of Financial Reporting at Mansour Investment Bank - Ali Adi Radhi Al Shamri (Indonesian Journal Publisher, 2025)
The study goals to assess the suitability of the necessities for implementing International Financial Reportage Standard (IFRS) 18 in the finance sector, analyze its bearing on improving the quality of financial commentary, and quantity the level of responsiveness and readiness of bank organization and workforces to implement it. It also studies the impact of its execution on civilizing the transparency, authority, and comparability of pecuniary statements. The study employed a descriptive-analytical approach, relying on published financial data and reports, as well as analyzing the availability of the necessary regulatory, technical, and human resources requirements for adopting IFRS 18. The impact of applying this standard on the quality characteristics of financial reports, namely relevance, reliability, comparability, and transparency, was also analyzed. The grades showed a perceptible positive impact of employing IFRS 18 on cultivating the quality of pecuniary reporting and ornamental the reliability of released accounting information. The study indorsed accelerating the homework of strategic plans for executing the standard, intensifying training sequencers, and enhancing discovery and transparency. This would underwrite to raising the productivity of banks' investment conclusions and increasing participant sureness.